Pengembangan Website E-Commerce memanfaatkan Metode Pembayaran Split Payment menggunakan API Payment Gateway (Studi Kasus: Media Ar-Raihan) - Dany Ahmad Ihza Prakoso; Buce Trias Hanggara; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Split payment is a payment method that uses the distribution of payment methods using more than one payment method. This payment method arises because of the consideration that in this day and age, buyers tend to have more than one account or digital wallet. Media Ar-Raihan is a bookstore located in Kraksaan, Probolinggo Regency, East Java that sells various Islamic book products, including Islamic Books with Salaf and reliable translations, Original Arabic Books, Arabic Learning Dictionary, and others. Based on the results of interviews with the owner of the Media Ar-Raihan bookstore, the ordering process at the Media Ar-Raihan bookstore is still manual using Instagram as a promotion and using WhatsApp as payment confirmation and the owner of the Media Ar-Raihan bookstore wants a payment method that makes it easy for users. From these problems the author intends to develop an e-commerce website that utilizes split payments as an alternative payment method and uses a payment gateway API. In its development, the author uses the waterfall method, starting with a literature study on e-commerce websites, payment gateways, and split payments. Then the needs analysis and system design are carried out where the authors describe UML diagrams, database design using Physical Data Model (PDM), and User Interface design using wireframes. Then the implementation includes the implementation of the database using the MySQL DBMS, the implementation of the program code using the PHP programming language and utilizing the Laravel framework. Then carried out 3 types of testing including Blackbox testing. In this test get an assessment of 100% accepted. Then there is the Compatibility test. This test got major issues and minor issues on several browsers such as IE, Firefox, and Safari. But this does not interfere with the integrity of the content submitted. Then the next test is User Acceptance Testing (UAT). The test got a value of 90% on the admin actor and 86 on the user actor